Effect of COVID-19 on Male Reproductive System – A Systematic Review - He, Yanfei; Wang, Jie; Ren, Junlin; Zhao, Yubo; Chen, Jing; Chen, Xuejiao (Frontiers in Endocrinology, 2021)
Background: Angiotensin-converting enzyme II (ACE2), a receptor for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) to enter host cells, is widely expressed in testes and prostate tissues. The testis and prostate produce semen. At present, there are contradictory reports about whether SARS-CoV-2 can exist in the semen of infected men. Objective: To provide a comprehensive overview of the topic of whether SARS-CoV-2 can impact on male reproductive system. Methods: We reviewed the relevant publications on the possible impact of Coronavirus Disease 2019 (COVID-19) on male reproductive system and summarized the latest and most important research results so far. Literature published in English from December 2019 to January 31, 2021 regarding the existence of SARS-CoV-2 in semen, testis, and prostatic fluid and the effects of COVID-19 on male reproductive were included. Results: We identified 28 related studies, only one of which reported the presence of SARS-CoV-2 in semen. The study found that the semen quality of patients with moderate infection was lower than that of patients with mild infection and healthy controls. The impaired semen quality may be related to fever and inflammation. Pathological analysis of the testis/epididymis showed that SARS-CoV-2 viral particles were positive in 10 testicular samples, and the spermatogenic function of the testis was impaired. All 94 expressed prostatic secretion (EPS) samples were negative for SARS-CoV-2 RNA. Conclusion: The likelihood of SARS-CoV-2 in the semen of COVID-19 patients is very small, and semen should rarely be regarded as a carrier of SARS-CoV-2 genetic material. However, COVID-19 may cause testicular spermatogenic dysfunction via immune or inflammatory reactions. Long-term follow-up is needed for COVID-19 male patients and fetuses conceived during the father's infection period.